Organización Contable en el Restaurant “La Castellana” de la ciudad de Loja, periodo abril – junio 2022. - Castillo Sánchez., Anthony José (2023)
The Curricular Integration Work called Accounting Organization in the Restaurant "La Castellana" of the city of Loja, period april - june 2022, is aimed at applying accounting tools to improve the development of the business under study, which allows knowing exactly the situation economic and financial, through the presentation of the Financial Statements. In the development of the investigative work, the proposed objectives were met, through the realization of a plan and manual of accounts according to the needs of the business, which facilitates the registration of economic activities; the lifting of inventories through physical verification of goods and values, with this the execution of the initial situation statement, auxiliary books of purchases, sales, daily book, general ledger, trial balance, work sheet, income statement, situation statement , cash flow statement and explanatory notes. With the accounting organization applied to the "La Castellana" restaurant, reliable, useful and timely financial information was obtained, reflected in the Financial Statements where a net profit for the year of $169,80 was determined; an asset of $19.109,16; a liability of $2.494,57 and equity of $16.444,80, information that is important for its owner to help him make appropriate decisions based on the economic growth of the business. Among the main conclusions, the execution of the accounting process can be established until obtaining the Financial Statements that will provide information to know the economic situation in which the business is located, for which it is recommended to carry out the accounting process established in the present work for to be able to have a better management of financial information and to be able to determine the current situation, which in turn allows making the most pertinent decisions for the business.